Design of Low-Power Structural FIR Filter Using Data-Driven Clock Gating and Multibit Flip-Flops. (10th July 2020) - Touil, Lamjed; Hamdi, Abdelaziz; Gassoumi, Ismail; Mtibaa, Abdellatif
Abstract : Optimization for power is one of the most important design objectives in modern digital signal processing (DSP) applications. The digital finite duration impulse response (FIR) filter is considered to be one of the most essential components of DSP, and consequently a number of extensive works had been carried out by researchers on the power optimization of the filters. Data-driven clock gating (DDCG) and multibit flip-flops (MBFFs) are two low-power design methods that are used and often treated separately. The combination of these methods into a single algorithm enables further power saving of the FIR filter. The experimental results show that the proposed FIR filter achieves 25% and 22% power consumption reduction compared to that using the conventional design.